(untitled) (Advances in Military Technology, 2022)
The paper deals with dilemma of the linear image field of view of the optoelectronic system which is intended for the measurement of the location of remote optical radiation sources. There is a brief description of the lay-out of the detection assemblage and conditions which have to be guaranteed to achieve the pulse position modulation which is needed to the objects detection responsive to the location. The importance of the field of view for jamming resistance and the feasibility of the field of view reduction by the electronic method is explained. This paper also deals with objects discrimination in image data using position prediction. To predict the object position in pictures sequence, principles of Kalman filtration are used. Objects discrimination is realised for matching true and predicted trajectories, when in case of their deviation the object is eliminated.